2004
DOI: 10.1097/01.mcg.0000129058.69524.90
|View full text |Cite
|
Sign up to set email alerts
|

Mid-esophageal Ulceration and Candidiasis-associated Distal Esophagitis as Two Distinct Clinical Patterns of Tetracycline or Doxycycline-induced Esophageal Injury

Abstract: The type of tetracyclines used by patients may give some clues to physicians on the pattern of esophageal injury because mid-esophageal ulceration seems to be more frequently associated with doxycycline and distal esophagitis with or without candidiasis with tetracycline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
2
14
0
1
Order By: Relevance
“…Despite the absence of strictures, dysphagia was the commonest in our case series which is similar to the findings in Saudi Arabia [4]. Symptoms typically get better within a few days of discontinuing doxycycline as was seen in our cases but protracted courses up to six weeks have been reported [5].…”
Section: Discussionsupporting
confidence: 73%
“…Despite the absence of strictures, dysphagia was the commonest in our case series which is similar to the findings in Saudi Arabia [4]. Symptoms typically get better within a few days of discontinuing doxycycline as was seen in our cases but protracted courses up to six weeks have been reported [5].…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies showed carvacrol as a potent and cost-effective agent against periodontal pathogens providing an adjunct mechanism that inhibits periodontal pocket formation (Osakawa et al, 1990;Botelho et al, in press). The local administration of carvacrol minimizes gastrointestinal side effects usually associated with longterm tetracycline administration (Gencosmanoglu et al, 2004). The use of locally delivered gel, such as carvacrol gel is an important adjunct for the treatment of periodontal disease drugs (Machion et al, 2006); In the present study, a significant (P < 0.05) decrease in the alveolar bone loss in the CAG group was observed as compared to vehicle-treated rats (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Common reason of this complication has been taking medications just before bedtime, and with a small amount of water [ 1 , 2 ]. In general the certain drugs tend to cause the damage in a singular segment, as doxycycline in mid-esophageal segment [ 3 ]. Here we present a severe, unusual endoscopic appearance of a case of doxycycline-induced esophageal ulcers and tissue fragility mimicking esophageal cancer in the lower and mid-esophageal segments, simultaneously.…”
Section: Introductionmentioning
confidence: 99%